Dynamics of Transmigration Policy as Supporting Policy of Palm Oil Plantation Development in Indonesia - Bondan Widyatmoko; Rosita Dewi (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2019)
Transmigration is the program which cannot be separated with the success story of palm oil development in Indonesia. Transmigrants becomes the engine to build the palm oil smallholder. The involvement of transmigrant in the PIR-Trans program, primary credit for member Scheme (KKPA), and revitalization scheme has been accelerating the palm oil plantation development in Indonesia. However, the “success” of developing palm oil plantation in Indonesia through scheme mentioned above was not without flaws. Unclear of land status or overlapping claim become the biggest problems faced nowadays. This paper aims to observe the development transmigration program and palm oil development in Indonesia. By analyzing policies of both transmigration programs and palm oil development from different political administration, this paper shows that, first, transmigration policy went from narrative of security, economic growth to border development and security. Second, under those different policy narratives, transmigration policy has been accommodated to the development of palm oil in Indonesia. Transfer of central authority to local government in executing transmigration movement and settlement has been addition to local government operational permission authority for palm oil development.